Effect of β-D-Mannuronic Acid (M2000) on Oxidative Stress Enzymes’ Gene Using Healthy Donor Peripheral Blood Mononuclear Cells for Evaluating the Anti-Aging Property - Taeb, Mahsa; Jafarzadeh, Abdollah; Mortazavi-Jahromi, Seyed S.; Zainodini, Nahid; Mirzaei, Mohammad Reza; Jafarnezhad-Ansariha, Fahimeh; Aghazadeh, Zahra; Mirshafiey, Abbas (Current Drug Discovery Technologies, 2019)
Objective: This research aimed to study the anti-aging and anti-inflammatory effects of low and high doses of the β-D-mannuronic (M2000) on gene expression of enzymes involved in oxidative stress (including SOD2, GST, GPX1, CAT, iNOS, and MPO) in peripheral blood mononuclear cells (PBMCs) of healthy donors under in vitro conditions. Methods: The PBMCs were separated and the RNAs were then extracted and the cDNAs synthesized, and expression levels of the mentioned genes were detected by qRT-PCR. Results: Our results indicated that the high dose of this drug could significantly reduce the expression level of the SOD2 gene compared to the lipopolysaccharide (LPS) group (p < 0.0001). Moreover, it was found that the high dose of this drug could significantly decrease the expression level of the GST gene compared to the LPS group (p < 0.0001). However, no significant reductions were observed in expression levels of the CAT and GPX1 genes compared to the LPS group. Furthermore, our data revealed that the level of iNOS and MPO gene expression was significantly reduced, in both doses of M2000, respectively, compared to the LPS group (p < 0.0001). Conclusion: This research showed that M2000 as a novel NSAID with immunosuppressive properties could modify oxidative stress through lowering expression levels of the SOD2, GST, iNOS, and MPO genes compared to the healthy expression levels, with a probable reduction of the risk of developing inflammatory diseases related to age and aging.
Keywords: oxidative stress